Hubungan Pengetahuan Ibu Tentang Makanan Pendamping ASI (MP-ASI) Dengan Kejadian Stunting pada Balita Diposyandu Wilayah Kerja Puskesmas Bangetayu Semarang - Siti Maulid Diyah; Iwan Ardian; Nutrisia Nu’im Haiya (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2026)
Stunting is a chronic nutritional disorder characterized by a child’s height being below the age-standard growth curve. One contributing factor is the mother’s knowledge regarding proper complementary feeding (MP-ASI). This study aims to determine the correlation between maternal knowledge of complementary feeding and stunting among children under five at Posyandu in the Bangetayu Health Center working area, Semarang. This research employed an analytical observational design with a case-control approach. A total of 60 respondents were selected using purposive sampling, consisting of 30 stunted and 30 non-stunted children. Data were collected using a structured questionnaire and analyzed using the Chi-Square test. The findings indicated that most mothers possessed good knowledge of complementary feeding (80%). Stunting prevalence among respondents was 41.7%. The Chi-Square test revealed a p-value of 0.000 (p < 0.05), demonstrating a significant relationship between maternal knowledge of complementary feeding and stunting. Mothers with poor knowledge were more likely to have stunted children compared to those with adequate understanding. These results highlight the crucial role of improving maternal nutrition knowledge to prevent stunting and support optimal child growth and development.